Clinicopathological Profile of Lung Cancer Patients - Bhandari, Pradip (Journal of Nobel Medical College, 2026)
Background: Lung cancer is a common malignancy and an important cause of cancer-related mortality. Institutional data from Eastern Nepal are limited.Materials and Methods: A descriptive hospital-based cross-sectional study was conducted in the Clinical Oncology Department of Nobel Medical College Teaching Hospital, Biratnagar, Nepal. Records of 50 confirmed lung cancer patients registered from January 2023 to December 2023 were reviewed. Data were retrieved from the oncology registry and hospital medical records and analyzed using descriptive statistics.Results: The mean age was 63.6 ± 11.3 years, with a median age of 68 years (range 27-79 years). Males and females were equally represented (25 each, 50.0%). Stage IV disease was observed in 30 (60.0%) patients and Stage III disease in 20 (40.0%) patients. Adenocarcinoma was the most common histological subtype (22, 44.0%), followed by squamous cell carcinoma (16, 32.0%) and small cell carcinoma (4, 8.0%). Smoking history was present in 35 (70.0%) patients.Conclusion: Lung cancer patients attending Nobel Medical College Teaching Hospital predominantly presented at advanced stages, and adenocarcinoma was the leading histological subtype.